2004
DOI: 10.1590/s1413-86702004000100006
|View full text |Cite
|
Sign up to set email alerts
|

Gatifloxacin in the treatment of community-acquired pneumonias: a comparative trial of ceftriaxone, with or without macrolides, in hospitalized adult patients with mild to moderately severe pneumonia

Abstract: Community-acquired pneumonia is very common, but some of the cases do require hospitalization for treatment, particularly when older patients and/or co-morbidities are involved; both "typical" and "atypical" respiratory pathogens take part etiologically, and there is increasing concern about the emergence of resistance. There is interest in therapeutic options that can: a) comprehend such a spectrum of bacteria and resistance; b) allow parenteral to oral sequential treatment. We made a multicenter, prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Nine of the 15 studies evaluated antibiotic regimens. Four of the eight RCTs evaluating antibiotics found no difference in clinical efficacy when comparing the following antibiotic regimens: gatifloxacin vs ceftriaxone (92% and 88% cure rate; P -value not reported), biapenem vs meropenem (94.7% vs 93.75% clinical efficacy; P -value not reported), levofloxacin five day vs seven day course (cure rate 56% vs 56.8%; difference = -0.8; 95% CI = -13.9 to 12.3) and levofloxacin vs ceftriaxone with azithromycin (hospital LOS 3.3 vs 3.4; P = 0.15) [ 59 , 61 , 63 , 64 ]. Abengowe et al [ 57 ] found higher cure rates (68.2% vs 36.5%; P < 0.01) with TMP-SMX over tetracycline in Nigeria, and Chaudhary et al [ 58 ] found benefit for ceftazidime-tobramycin over ceftriaxone in India (88.4% vs 61.2%; P -value not reported), although with high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the 15 studies evaluated antibiotic regimens. Four of the eight RCTs evaluating antibiotics found no difference in clinical efficacy when comparing the following antibiotic regimens: gatifloxacin vs ceftriaxone (92% and 88% cure rate; P -value not reported), biapenem vs meropenem (94.7% vs 93.75% clinical efficacy; P -value not reported), levofloxacin five day vs seven day course (cure rate 56% vs 56.8%; difference = -0.8; 95% CI = -13.9 to 12.3) and levofloxacin vs ceftriaxone with azithromycin (hospital LOS 3.3 vs 3.4; P = 0.15) [ 59 , 61 , 63 , 64 ]. Abengowe et al [ 57 ] found higher cure rates (68.2% vs 36.5%; P < 0.01) with TMP-SMX over tetracycline in Nigeria, and Chaudhary et al [ 58 ] found benefit for ceftazidime-tobramycin over ceftriaxone in India (88.4% vs 61.2%; P -value not reported), although with high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…WHO created standardized case management guidelines (IMCI), which suggest that children with severe pneumonia, which is determined by the presence of lower chest wall indrawing (LCI), be admitted to a hospital and treated with parenteral antibiotics (penicillin G or ampicillin) (World Health Organization 2005a). This will help decrease child mortality from pneumonia and rationalize antibiotic treatment [83].…”
Section: Inpatient Carementioning
confidence: 99%